A Logical Approach to the Effect of Social Identity Motivation in Crimes Against Humanity - Abdulkadir Nacar (Public and Private International Law Bulletin)
After World War II, crimes against humanity found application in the international and national level. If we look conceptually and terminologically, we encounter a process that goes back to World War II. It is possible to make a “definition” that refers to “humanity” for the actions that these crimes refer to, by testing them from various perspectives because a definition is a compulsory tool of logic to create and strengthen the concept. Crimes against humanity, both historically, theoretically, and in the context of judicial practices, point to an inconsistent concept. Indeed, this inconsistency was expressed by competent criminal law jurists in the sense that the definition of crimes against humanity has drawbacks. Based on this, the study is grounded on a set of principles that classical logic offers for definitions while analyzing the drawbacks of the concept. As a result of this analysis, the study found that there is a clear social identity motive in acts called crimes against humanity.The social identity approach recognizes that certain correlations can be established in the cognitive and behavioral states of individuals within a group. These correlations allow us to have an idea about the emergence and sustainability of group behavior, the needs of social groups, their relationship with individual identities and social cohesion. When crimes against humanity are simply reduced to the grounds of discrimination, and discrimination is expressed as social identity-based behavior, the importance of social groups will emerge. In other words, social groups, by constructing the social identities, determine the presumptions that are the reference of the perpetrator in crimes against humanity. The study identifies this context and reveals that the acts of crime against humanity are actually qualified forms of the relevant offenses that manifest the social identity motivation. Since states have specific construction processes of social identities, a normative and judicial system based on testable social psychology data is recommended at the national level.